Added value of invasive needle techniques in mediastinal and hilar nodal staging of clinical N0-N1 non-small cell lung cancer after positron emission tomography. (September 2020) - Collin-Castonguay, Marie-May; Guinde, Julien; Laflamme, Laurie; Marcoux, Sabrina; Fortin, Marc
Abstract: Previous studies evaluating staging methods of lung cancer have focused on mediastinal disease. We explored the added value of endoscopic techniques after PET scan in the evaluation of N1 nodal stations in 276 patients with a radiologically normal mediastinum demonstrating a potential stage shift in 20% of patients.